2015
DOI: 10.1007/s00248-015-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Cyanide-Degrading Potential of Bacterial Community Associated with the Coking Wastewater Treatment Plant with a Novel Draft Genome

Abstract: Biotreatment processes fed with coking wastewater often encounter insufficient removal of pollutants, such as ammonia, phenols, and polycyclic aromatic hydrocarbons (PAHs), especially for cyanides. However, only a limited number of bacterial species in pure cultures have been confirmed to metabolize cyanides, which hinders the improvement of these processes. In this study, a microbial community of activated sludge enriched in a coking wastewater treatment plant was analyzed using 454 pyrosequencing and Illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…Similar to the results of this study, the dominance of Betaproteobacteria (higher taxa) has been frequently observed in phenol degradation systems, including CWW (Manefield et al 2005;Zhu et al 2013Zhu et al , 2016Ma et al 2015a;Wang et al 2015b) petroleum refinery, pharmaceutical (Ibarbalz et al 2013), and municipal Wang et al 2012;Hai et al 2014;Shu et al 2015) wastewater treatment plants, as well as in different types of bioreactors (Wagner and Loy 2002). This highlights the rapid a c c l i m a t i z a t i o n a n d m e t a b o l i c s i g n i f i c a n c e o f Betaproteobacteria in the removal of a wide range of pollutants, including phenolic compounds from CWW.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the results of this study, the dominance of Betaproteobacteria (higher taxa) has been frequently observed in phenol degradation systems, including CWW (Manefield et al 2005;Zhu et al 2013Zhu et al , 2016Ma et al 2015a;Wang et al 2015b) petroleum refinery, pharmaceutical (Ibarbalz et al 2013), and municipal Wang et al 2012;Hai et al 2014;Shu et al 2015) wastewater treatment plants, as well as in different types of bioreactors (Wagner and Loy 2002). This highlights the rapid a c c l i m a t i z a t i o n a n d m e t a b o l i c s i g n i f i c a n c e o f Betaproteobacteria in the removal of a wide range of pollutants, including phenolic compounds from CWW.…”
Section: Discussionsupporting
confidence: 89%
“…Since these microbial populations are associated with pollutant removal efficiency, understanding community structure in different stages during long-term operated CWW treatment is important. Previous studies have focused on bacterial diversity surveys in full-scale CWW treatment systems, revealing the distribution of potential degraders of phenols, SCN − , and CN − (Zhu et al , 2016Ma et al 2015a;Wang et al 2015b). However, to better understand the profiles of acclimatized bacterial, archaeal, and fungal communities associated with degradation of different pollutants, research on controlled sequential anaerobic and aerobic CWW treatment systems is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these results could be linked with the decrease of nitrogen removal efficacy which in biofilm systems can be performed at large scale by Anammox process performed by Planctomycetia . In case the of activated sludge classes, Firmicutes , Chlorobi , and Chloroflexi are often dominant in the system (Felföldi et al 2010 ; Ma et al 2015 ; Wang et al 2015 ), while for biofilm, these classes are not recognized as the main groups.…”
Section: Resultsmentioning
confidence: 99%
“…Por otro lado, la metagenómica se resalta como una herramienta importante para la biorremediación (Gabor et al 2007, George et al 2011, permitiendo entender la estructura, interacción y potencial metabólico de las comunidades microbianas no cultivables, capaces de degradar cianuros (Wang et al 2015, Kantor et al 2015, Luque et al 2016. Los miembros del filo Proteobacteria son frecuentemente encontrados en suelos de diferentes tipos de minas (Moreels et al 2008, Khan et al 2013, Li et al 2014.…”
Section: Discussionunclassified